Antibodies Produced by CLL Phenotype B Cells in Patients With Myasthenia Gravis Are Not Directed Against Neuromuscular Endplates. Issue 2 (7th March 2023) - Ingelfinger, Florian; Kramer, Michael; Lutz, Mirjam; Widmer, Corinne C.; Piccoli, Luca; Kreutmair, Stefanie; Wertheimer, Tobias; Woodhall, Mark; Waters, Patrick; Sallusto, Federica; Lanzavecchia, Antonio; Mundt, Sarah; et al.
Abstract : Background and Objectives: Myasthenia gravis (MG) can in rare cases be an autoimmune phenomenon associated with hematologic malignancies such as chronic lymphocytic leukemia (CLL). It is unclear whether in patients with MG and CLL, the leukemic B cells are the ones directly driving the autoimmune response against neuromuscular endplates. Methods: We identified patients with acetylcholine receptor antibody–positive (AChR + ) MG and CLL or monoclonal B-cell lymphocytosis (MBL), a precursor to CLL, and described their clinical features, including treatment responses. We generated recombinant monoclonal antibodies (mAbs) corresponding to the B-cell receptors of the CLL phenotype B cells and screened them for autoantigen binding. Results: A computational immune cell screen revealed a subgroup of 5/38 patients with MG and 0/21 healthy controls who displayed a CLL-like B-cell phenotype. In follow-up hematologic flow cytometry, 2 of these 5 patients were diagnosed with an MBL. An additional patient with AChR + MG as a complication of manifest CLL presented at our neuromuscular clinic and was successfully treated with the anti-CD20 therapy obinutuzumab plus chlorambucil. We investigated the specificities of expanding CLL-like B-cell clones to assess a direct causal link between the 2 diseases. However, we observed no reactivity of the clones against the AChR, antigens at the neuromuscular junction, or other common autoantigens. Discussion: Our study suggests that AChR autoantibodies are produced by nonmalignant, polyclonal B cells The new anti-CD20 treatment obinutuzumab might be considered in effectively treating AChR + MG. Classification of Evidence: This is a single case study and provides Class IV evidence that obinutuzumab is safe to use in patients with MG.